2002
DOI: 10.1212/wnl.58.11.1698
|View full text |Cite
|
Sign up to set email alerts
|

SUNCT syndrome in two patients with prolactinomas and bromocriptine-induced attacks

Abstract: We report two patients with prolactin-secreting adenomas, SUNCT (short-lasting, unilateral neuralgiform headache attacks with conjunctival injection and tearing) syndrome, and bromocriptineinduced attacks.Case reports. Patient 1. A 40-year-old woman had her first headaches at age 27. The attacks consisted of a severe burning pain in the left parietal area, lasting 15 to 30 seconds. This was accompanied by conjunctival injection and tearing of the left eye, triggered by physical exercise or sexual activity. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
78
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 7 publications
1
78
1
Order By: Relevance
“…We found that the rise of serum PRL during attacks was not accompanied by a TSH rise. This case, along with other similar reports in the literature, supports the hypothalamic connection to this trigeminal autonomic cephalalgia [7]. The pathophysiology of SUNCT is unknown, though fMRI studies in attacks have documented activation of the ipsilateral hypothalamic grey [5].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the rise of serum PRL during attacks was not accompanied by a TSH rise. This case, along with other similar reports in the literature, supports the hypothalamic connection to this trigeminal autonomic cephalalgia [7]. The pathophysiology of SUNCT is unknown, though fMRI studies in attacks have documented activation of the ipsilateral hypothalamic grey [5].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, dopaminergic hypofunction could be the consequence of serotoninergic hyperfunction, because of the inhibitory effect of serotonin on dopamine neurons. In fact, in patients with SUNCT the treatment with dopamine-agonists can determine various responses, with worsening in some cases [7] and improvement in others [11,12]. Most cases of SUNCT syndrome are primary but several cases of SUNCT are secondary and occur in patients with pituitary tumours, further supporting involvement of the hypothalamic-hypophysial axis.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence shows that a tumour mass is not correlated to the presence or intensity of the headache, thus, the cause of the headache lies in something other than the volume of the tumour. The same concept was also considered by other authors who described the presence of headache in patients with microprolactinoma [15,16]. Referring to the type of headaches related to prolactinomas, the articles published up to now have cited cases of trigeminal autonomic cephalalgias (TACs) [15], short lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) [16,17] and migraine in only one case [17].…”
mentioning
confidence: 84%
“…The etiology is unknown, but recently cases secondary to cerebellopontine angle arteriovenous malformations 12,13 , brain stem cavernous hemangioma 14 , a posterior fossa lesion in a patient with AIDS 3 , prolactinomas 15 , and corneal lesion 16 have been described.…”
Section: Discussionmentioning
confidence: 99%